Factors influencing the stability of vitamin A in infant noodles - LI Qingqing; LIU Shuyi; LI Qiuyu; DAI Zhiyong (Shipin yu jixie)
ObjectiveTo clarify the main causes of vitamin A loss during the processing and storage of infant noodles.MethodsWheat flour with different protein contents was selected, and iron elements of different price ranges were added to prepare the straight strip-shaped noodles, butterflies-shaped noodles and extruded noodles. The effects of protein content, iron element, processing technology and packaging on vitamin A were studied.ResultsThe results showed that as the protein content in wheat flour decreased, the loss rate and attenuation rate of vitamin A in noodles gradually increased. Vitamin A had the fastest rate of attenuation rate in the first 10 days. Compared with the straight strip-shaped noodles and extruded noodles, the loss of vitamin A in the processing process of butterflies-shaped noodles was the least. Mixing dough with vacuum can significantly reduce the rate of vitamin A loss. Compared to ferrous fumarate, vitamin A was more stable in iron pyrophosphate. In addition, nitrogen filling in the packaging could effectively reduce the loss of vitamin A in infant noodles.ConclusionThe use of trivalent iron, mixing dough with vacuum, and nitrogen filled packaging in infant noodles can effectively ensure the stability of vitamin A in the noodles.